Protection against oxidation during dehydration of yeast - de Jesus Pereira, Elenilda (Cell Stress Society International, 2003)
Based on the well-documented notion that oxygen affects the stability of dried cells, the role of the cytosolic and mitochondrial forms of superoxide dismutase (Sod) in the capacity of cells to resist dehydration was examined. Both enzymes are important for improving survival, and the absence of only 1 isoform did not impair tolerance against dehydration. In addition, sod strains showed the same Sod activity as the control strain, indicating that the deficiency in either cytoplasmic Cu/Zn or mitochondrial Mn was overcome by an increase in activity of the remaining Sod. To measure the level of intracellular oxidation produced by dehydration, a fluorescent probe, 2′,7′-dichlorofluorescein, was used. Dry cells exhibited a high increase in fluorescence: both control and sod mutant strains became almost 10-fold more oxidized after dehydration. Furthermore, the disaccharide trehalose was shown to protect dry cells against oxidation.